BHLHE40 plays a pathological role in pre-eclampsia through upregulating SNX16 by transcriptional inhibition of miR-196a-5p. (24th June 2020) - Mi, Chunmei; Ye, Bin; Gao, Zhou; Du, Jinzhi; Li, Ruizhen; Huang, Dong
Abstract: Pre-eclampsia (PE), which results from abnormal placentation, is a primary cause of maternal and neonatal morbidity and mortality. However, the causes of abnormal development of the placenta remain poorly understood. BHLHE40 is a transcriptional repressor in response to hypoxia. Bioinformatics analysis demonstrated that BHLHE40 negatively regulates miR-196a-5p expression, which may decrease miR-196a-5p to target SNX16. Since SNX16 exerts an inhibitory effect on cell migration, it may disrupt trophoblast cell migration in placentation. Therefore, the objective of this study was to explore a possible role of the BHLHE40/miR-196a-5p/SNX16 axis in PE pathogenesis. BHLHE40, miR-196a-5p and SNX16 mRNA and/or protein levels were detected in PE and normal placenta tissues. PE models in vitro and in vivo were constructed by culturing trophoblasts under hypoxia and reducing the uterine perfusion pressure in pregnant C57/BL6N mice, respectively. BHLHE40 and SNX16 were upregulated in PE placenta, while miR-196a-5p was downregulated. Knockdown of BHLHE40 reversed miR-196a-5p expression in trophoblasts under hypoxia, and upregulation of miR-196a-5p inhibited SNX16 expression. As indicated by ChIP assay, BHLHE40 bound to the promoter of the miR-196a-5p gene; luciferase reporter analysis showed that miR-196a-5p could bind to the 3ʹ-untranslated region of SNX16 mRNA. Knockdown of either BHLHE40 or SNX16, or an increase in miR-196a-5p, restored cell viability, migration, invasion and matrix metalloprotein (MMP)-2 and MMP-9 expression under hypoxia. BHLHE40 knockdown also alleviated PE symptoms in pregnant C57/BL6N mice. This study supports involvement of the BHLHE40/miR-196a-5p/SNX16 axis in PE pathogenesis; Proper adjustment of the BHLHE40/miR-196a-5p/SNX16 axis is able to attenuate PE symptoms.